Fractal-Shaped Metamaterials and Applications to Enhanced-Performance Devices Exhibiting High Selectivity - He-Xiu Xu; Guang-Ming Wang; Chen-Xin Zhang (International Journal of Antennas and Propagation)
Novel single negative metamaterial (MTM) transmission lines (TLs) are presented and studied in microstrip technology. They consist of a host TL in the conductor strip and a fractal-shaped complementary ring resonator (CRR) etched in the ground plane. Two types of fractal-shaped CRR are involved including the Moore and Hilbert. It is found that fractal perturbation in CRR results in lower and more transmission zeros in comparison with conventional CRR using nonfractal geometries. The single negative-permeability or -permittivity of these MTM TLs which associated with the resultant multitransmission zeros occurs by turns and should benefit devices with high selectivity requirement. Potential application of these MTM cells are illustrated by two examples, one is the microstrip stepped-impedance transformers (SIT) operating at 3.5 GHz with two edged attenuation poles to introduce selectivity; the other one is the Hi-Lo microstrip low-pass filter (LPF) with cutoff frequency 2.5 GHz exhibiting improved selectivity (77.3 dB/GHz). By constructing the low-impedance sections as hybrid prefractal shape and crown square, both the SITs and LPF obtained additional bandwidth enhancement and good matching. Consistent results between simulation and measurement have confirmed the design concept.